Evaluation of natural alternative products in the control of varroa destructor in honey bees (Apis mellifera) - Airahuacho Bautista, Félix (2023)
The aim of this research was to evaluate the effect of alternative natural products in the control of Varroa destructor in honey bees (Apis mellifera) in an apiary located in Sayán, Lima region, Peru. Five treatments (oxalic acid, thymol, vaseline, tobacco and control) and six replications per treatment were used for 16 days. The hives with rates greater than 2% of varroa infestation were selected and the evaluations were carried out in the adult bee, operculated cells and floor of the hive at the beginning and end of the experiment. The Proportions Test was used to evaluate the effectiveness of the treatments in adult bees and in operculated cells, while the Kruskall-Wallis test and Dunn's post hoc test were used to evaluate dead varroa on the hive floor. When comparing the level of infestation at the beginning (day 0) and at the end of the experiment (day 16), oxalic acid, thymol and tobacco (p<0.05) were the most effective treatments for the control of varroa in the dispersal state and the oxalic acid the most efficient (p<0.05) in the control of varroas in operculated cells. When evaluating the effectiveness between treatments, oxalic acid was efficient to control varroa both in the dispersal state and in operculated cells (p<0.05), thymol was the best to control varroa in dispersion (p<0.05) and its efficiency to control varroa in operculated cells was lower than oxalic acid but higher than that of vaseline. The higher counts of varroa on the floor of the hives in the treatments with oxalic acid and thymol (p<0.05) coincide with the greater efficacy of these products in the control of varroa. Oxalic acid is shown as the best natural alternative for the control of varroa in the hive.